The title of this post is a play on the Lisp aphorism: "Code is Data". In the Lisp world everything is data; code is just another data structure that you can manipulate and transform.
However, you can also go to the exact opposite extreme: "Data is Code"! You can make everything into code and implement data structures in terms of code.
You might wonder what that even means: how can you write any code if you don't have any primitive data structures to operate on? Fascinatingly, Alonzo Church discovered a long time ago that if you have the ability to define functions you have a complete programming language. "Church encoding" is the technique named after his insight that you could transform data structures into functions.
This post is partly a Church encoding tutorial and partly an announcement for my newly released annah
compiler which implements the Church encoding of data types. Many of the examples in this post are valid annah
code that you can play with. Also, to be totally pedantic annah
implements BoehmBerarducci encoding which you can think of as the typed version of Church encoding.
This post assumes that you have basic familiarity with lambda expressions. If you do not, you can read the first chapter (freely available) of the Haskell Programming from First Principles
which does an excellent job of teaching lambda calculus.
If you would like to follow along with these examples, you can download and install annah
by following these steps:

Install
thestack
tool 
Create the following
stack.yaml
file$ cat > stack.yaml resolver: lts5.13 packages: [] extradeps:  annah1.0.0  morte1.6.0

Run
stack setup

Run
stack install annah

Add the installed executable to your
$PATH
Lambda calculus
In the untyped lambda calculus, you only have lambda expressions at your disposal and nothing else. For example, here is how you encode the identity function:
λx → x
That's a function that takes one argument and returns the same argument as its result.
We call this "abstraction" when we introduce a variable using the Greek lambda symbol and we call the variable that we introduce a "bound variable". We can then use that "bound variable" anywhere within the "body" of the lambda expression.
+ Abstraction

+ Bound variable

vv
λx → x
^

+ Body of lambda expression
Any expression that begins with a lambda is an anonymous function which we can apply to another expression. For example, we can apply the the identity function to itself like this:
(λx → x) (λy → y)
 βreduction
= λy → y
We call this "application" when we supply an argument to an anonymous function.
We can define a function of multiple arguments by nested "abstractions":
λx → λy → x
The above code is an anonymous function that returns an anonymous function. For example, if you apply the outermost anonymous function to a value, you get a new function:
(λx → λy → x) 1
 βreduce
λy → 1
... and if you apply the lambda expression to two values, you return the first value:
(λx → λy → x) 1 2
 βreduce
(λy → 1) 2
 βreduce
1
So our lambda expression behaves like a function of two arguments, even though it's really a function of one argument that returns a new function of one argument. We call this "currying" when we simulate functions of multiple arguments using functions one argument. We will use this trick because we will be programming in a lambda calculus that only supports functions of one argument.
Typed lambda calculus
In the typed lambda calculus you have to specify the types of all function arguments, so you have to write something like this:
λ(x : a) → x
... where a
is the type of the bound variable named x
.
However, the above function is still not valid because we haven't specified what the type a
is. In theory, we could specify a type like Int
:
λ(x : Int) → x
... but the premise of this post was that we could program without relying on any builtin data types so Int
is out of the question for this experiment.
Fortunately, some typed variations of lambda calculus (most notably: "System F") let you introduce the type named a
as yet another function argument:
λ(a : *) → λ(x : a) → x
This is called "type abstraction". Here the *
is the "type of types" and is a universal constant that is always in scope, so we can always introduce new types as function arguments this way.
The above function is the "polymorphic identity function", meaning that this is the typed version of the identity function that still preserves the ability to operate on any type.
If we had builtin types like Int
we could apply our polymorphic function to the type just like any other argument, giving back an identity function for a specific type:
(λ(a : *) → λ(x : a) → x) Int
 βreduction
λ(x : Int) → x
This is called "type application" or (more commonly) "specialization". A "polymorphic" function is a function that takes a type as a function argument and we "specialize" a polymorphic function by applying the function to a specific type argument.
However, we are forgoing builtin types like Int
, so what other types do we have at our disposal?
Well, every lambda expression has a corresponding type. For example, the type of our polymorphic identity function is:
∀(a : *) → ∀(x : a) → a
You can read the type as saying:
 this is a function of two arguments, one argument per "forall" (∀) symbol

the first argument is named
a
anda
is a type 
the second argument is named
x
and the type ofx
isa

the result of the function must be a value of type
a
This type uniquely determines the function's implementation. To be totally pedantic, there is exactly one implementation up to extensional equality of functions
. Since this function has to work for any possible type a
there is only one way to implement the function. We must return x
as the result, since x
is the only value available of type a
.
Passing around types as values and function arguments might seem a bit strange to most programmers since most languages either:

do not use types at all
Example: Javascript
// The polymorphic identity function in Javascript function id(x) { return x } // Example use of the function id(true)

do use types, but they hide type abstraction and type application from the programmer through the use of "type inference"
Example: Haskell
 The polymorphic identity function in Haskell id x = x  Example use of the function id True

they use a different syntax for type abstraction/application versus ordinary abstraction and application
Example: Scala
 The polymorphic identity function in Scala def id[A](x : a)  Example use of the function  Note: Scala lets you omit the `[Boolean]` here thanks  to type inference but I'm making the type  application explicit just to illustrate that  the syntax is different from normal function  application id[Boolean](true)
For the purpose of this post we will program with explicit
type abstraction and type application so that there is no magic or hidden machinery.
So, for example, suppose that we wanted to apply the typed, polymorphic identity function to itself. The untyped version was this:
(λx → x) (λy → y)
... and the typed version is this:
(λ(a : *) → λ(x : a) → x)
(∀(b : *) → ∀(y : b) → b)
(λ(b : *) → λ(y : b) → y)
 βreduction
= (λ(x : ∀(b : *) → ∀(y : b) → b) → x)
(λ(b : *) → λ(y : b) → y)
 βreduction
= (λ(b : *) → λ(y : b) → y)
So we can still apply the identity function to itself, but it's much more verbose. Languages with type inference automate this sort of tedious work for you while still giving you the safety guarantees of types. For example, in Haskell you would just write:
(x > x) (y > y)
... and the compiler would figure out all the type abstractions and type applications for you.
Exercise:Haskell provides a const
function defined like this:
const :: a > b > a
const x y = x
Translate const
function to a typed and polymorphic lambda expression in System F (i.e. using explicit type abstractions)
Boolean values
Lambda expressions are the "code", so now we need to create "data" from "code".
One of the simplest pieces of data is a boolean value, which we can encode using typed lambda expressions. For example, here is how you implement the value True
:
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
Note that the names have no significance at all. I could have equally well written the expression as:
λ(a : *) → λ(x : a) → λ(y : a) → x
... which is "αequivalent" to the previous version (i.e. equivalent up to renaming of variables).
We will save the above expression to a file named ./True
in our current directory. We'll see why shortly.
We can either save the expression using Unicode characters:
$ cat > ./True
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
... or using ASCII, replacing each lambda (i.e. λ
) with a backslash (i.e.
) and replacing each arrow (i.e. →
) with an ASCII arrow (i.e. >
)
$ cat > ./True
(Bool : *) > (True : Bool) > (False : Bool) > True
... whichever you prefer. For the rest of this tutorial I will use Unicode since it's easier to read.
Similarly, we can encode False
by just changing our lambda expression to return the third argument named False
instead of the second argument named True
. We'll name this file ./False
:
$ cat > ./False
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
What's the type of a boolean value? Well, both the ./True
and ./False
files have the same type, which we shall call ./Bool
:
$ cat > ./Bool
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
... and if you are following along with ASCII you can replace each forall symbol (i.e. ∀
) with the word forall
:
$ cat > ./Bool
forall (Bool : *) > forall (True : Bool) > forall (False : Bool) > Bool
We are saving these terms and types to files because we can use the annah
compiler to work with any lambda expression or type saved as a file. For example, I can use the annah
compiler to verify that the file ./True
has type ./Bool
:
$ annah
 Read this as: "./True has type ./Bool"
./True : ./Bool
./True
$ echo $?
0
If the expression typechecks then annah
will just compile the expression to lambda calculus (by removing the unnecessary type annotation in this case) and return a zero exit code. However, if the expression does not typecheck:
$ annah
./True : ./True
annah:
Expression: ∀(x : λ(Bool : *) → λ(True : Bool) → λ(False : Bool)
→ True) → λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
Error: Invalid input type
Type: λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
$ echo $?
1
... then annah
will throw an exception and return a nonzero exit code. In this case annah
complains that the ./True
on the righthand side of the type annotation is not a valid type.
The last thing we need is a function that can consume values of type ./Bool
, like an ./if
function:
$ cat > ./if
λ(x : ./Bool ) → x
 ^
 
 + Note the space. Filenames must end with a space
The definition of ./if
is blindingly simple: ./if
is just the identity function on ./Bool
s!
To see why this works, let's see what the type of ./if
is. We can ask for the type of any expression by feeding the expression to the morte
compiler via standard input:
$ morte < ./if
∀(x : ∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool) →
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(x : ∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool) → x
morte
is a lambda calculus compiler installed alongside annah
and annah
is a higherlevel interface to the morte
language. By default, the morte
compiler will:
 resolve all file references (transitively, if necessary)
 typecheck the expression
 optimize the expression
 write the expression's type to standard error as the first line of output
 write the optimized expression to standard output as the last line of output
In this case we only cared about the type, so we could have equally well just asked the morte
compiler to resolve and infer the type of the expression:
$ morte resolve < ./Bool/if  morte typecheck
∀(x : ∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool) →
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
The above type is the same thing as:
∀(x : ./Bool ) → ./Bool
If you don't believe me you can prove this to yourself by asking morte
to resolve the type:
$ echo "∀(x : ./Bool ) → ./Bool"  morte resolve
∀(x : ∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool) →
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
However, the type will make the most sense if you only expand out the second ./Bool
in the type but leave the first ./Bool
alone:
./Bool → ∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
You can read this type as saying that the ./if
function takes four arguments:

the first argument is the
./Bool
that we want to branch on (i.e../True
or./False
) 
the second argument is the result type of our
./if
expression 
the third argument is the result we return if the
./Bool
evaluates to./True
(i.e. the "then" branch) 
the fourth argument is the result we return if the
./Bool
evaluates to./False
(i.e. the "else" branch)
For example, this Haskell code:
if True
then False
else True
... would translate to this Annah code:
$ annah
./if ./True
./Bool  The type of the result
./False  The `then` branch
./True  The `else` branch
./if ./True ./Bool ./False ./True
annah
does not evaluate the expression. annah
only translates the expression into Morte code (and the expression is already valid Morte code) and typechecks the expression. If you want to evaluate the expression you need to run the expression through the morte
compiler, too:
$ morte
./if ./True
./Bool  The type of the result
./False  The `then` branch
./True  The `else` branch
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
morte
deduces that the expression has type ./Bool
and the expression evaluates to ./False
.
morte
evaluates the expression by resolving all references and repeatedly applying βreduction. This is what happens under the hood:
./if
./True
./Bool
./False
./True
 Resolve the `./if` reference
= (λ(x : ./Bool ) → x)
./True
./Bool
./False
./True
 βreduce
= ./True
./Bool
./False
./True
 Resolve the `./True` reference
= (λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True)
./Bool
./False
./True
 βreduce
= (λ(True : ./Bool ) → λ(False : ./Bool ) → True)
./False
./True
 βreduce
= (λ(False : ./Bool ) → ./False )
./True
 βreduce
= ./False
 Resolve the `./False` reference
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
The above sequence of steps is a white lie: the true order of steps is actually different, but equivalent.
The ./if
function was not even necessary because every value of type ./Bool
is already a "preformed if expression". That's why ./if
is just the identity function on ./Bool
s. You can delete the ./if
from the above example and the code will still work.
Now let's define the not
function and save the function to a file:
$ annah > ./not
λ(b : ./Bool ) →
./if b
./Bool
./False  If `b` is `./True` then return `./False`
./True  If `b` is `./False` then return `./True`
We can now use this file like an ordinary function:
$ morte
./not ./False
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
$ morte
./not ./True
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
Notice how ./not ./False
returns ./True
and ./not ./True
returns ./False
.
Similarly, we can define an and
function and an or
function:
$ annah > and
λ(x : ./Bool ) → λ(y : ./Bool ) →
./if x
./Bool
y  If `x` is `./True` then return `y`
./False  If `x` is `./False` then return `./False`
<CtrlD>
$ annah > or
λ(x : ./Bool ) → λ(y : ./Bool ) →
./if x
./Bool
./True  If `x` is `./True` then return `./True`
y  If `x` is `./False` then return `y`
<CtrlD>
... and use them:
$ morte
./and ./True ./False
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
$ morte
./or ./True ./False
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
We started with nothing but lambda expressions, but still managed to implement:

a
./Bool
type 
a
./True
value of type./Bool

a
./False
value of type./Bool

./if
,./not
,./and
, and./or
functions
... and we can do real computation with them! In other words, we've modeled boolean data types entirely as code.
Exercise:Implement an xor
function
Natural numbers
You might wonder what other data types you can implement in terms of lambda calculus. Fortunately, you don't have to wonder because the annah
compiler will actually compile data type definitions to lambda expressions for you.
For example, suppose we want to define a natural number type encoded using Peano numerals. We can write:
$ annah types
type Nat
data Succ (pred : Nat)
data Zero
fold foldNat
You can read the above datatype specification as saying:

Define a type named
Nat
... 
... with a constructor named
Succ
with one field namedpred
of typeNat
... 
... with another constructor named
Zero
with no fields 
... and a fold named
foldNat
annah
then translates the datatype specification into the following files and directories:
+ ./Nat.annah  `annah` implementation of `Nat`

` ./Nat

+ @  `morte` implementation of `Nat`
 
  If you import the `./Nat` directory this file is
  imported instead

+ Zero.annah  `annah` implementation of `Zero`

+ Zero  `morte` implementation of `Zero`

+ Succ.annah  `annah` implementation of `Succ`

+ Succ  `morte` implementation of `Succ`

+ foldNat.annah  `annah` implementation of `foldNat`

` foldNat  `morte` implementation of `foldNat`
Let's see how the Nat
type is implemented:
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
All BoehmBerarducciencoded datatypes are encoded as substitution functions, including ./Nat
. Any value of ./Nat
is a function that takes three arguments that we will substitute into our natural number expression:

The first argument replace every occurrence of the
Nat
type 
The second argument replaces every occurrence of the
Succ
constructor 
The third argument replaces every occurrence of the
Zero
constructor
This will make more sense if we walk through a specific example. First, we will build the number 3 using the ./Nat/Succ
and ./Nat/Zero
constructors:
$ morte
./Nat/Succ (./Nat/Succ (./Nat/Succ ./Nat/Zero ))
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ Zero))
Now suppose that we want to compute whether or not our natural number is even
. The only catch is that we must limit ourselves to substitution when computing even
. We have to figure out something that we can substitute in place of the Succ
constructors and something that we can substitute in place of the Zero
constructors that will then evaluate to ./True
if the natural number is even
and ./False
otherwise.
One substitution that works is the following:

Replace every
Zero
with./True
(becauseZero
iseven
) 
Replace every
Succ
with./not
(becauseSucc
alternates betweeneven
andodd
)
So in other words, if we began with this:
./Nat/Succ (./Nat/Succ (./Nat/Succ ./Nat/Zero ))
... and we substitute with ./Nat/Succ
with ./not
and substitute ./Nat/Zero
with ./True
:
./not (./not (./not ./True ))
... then the expression will reduce to ./False
.
Let's prove this by saving the above number to a file named ./three
:
$ morte > ./three
./Nat/Succ (./Nat/Succ (./Nat/Succ ./Nat/Zero ))
$ cat three
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ Zero))
The first thing we need to do is to replace the Nat
with ./Bool
:
./three ./Bool
 Resolve `./three`
= (λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ Zero))
) ./Bool
 βreduce
= λ(Succ : ∀(pred : ./Bool ) → ./Bool ) → λ(Zero : ./Bool ) →
Succ (Succ (Succ Zero))
Now the next two arguments have exactly the right type for us to substitute in ./not
and ./True
. The argument named ./Succ
is now a function of type ∀(pred : ./Bool ) → ./Bool
, which is the same type as ./not
. The argument named Zero
is now a value of type ./Bool
, which is the same type as ./True
. This means that we can proceed with the next two arguments:
./three ./Bool ./not ./True
 Resolve `./three`
= (λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ Zero))
) ./Bool ./not ./True
 βreduce
= (λ(Succ : ∀(pred : ./Bool ) → ./Bool ) → λ(Zero : ./Bool ) →
Succ (Succ (Succ Zero))
) ./not ./True
 βreduce
= (λ(Zero : ./Bool ) → ./not (./not (./not Zero))) ./True
 βreduce
= ./not (./not (./not ./True )))
The result is exactly what we would have gotten if we took our original expression:
./Nat/Succ (./Nat/Succ (./Nat/Succ ./Nat/Zero ))
... and replaced ./Nat/Succ
with ./not
and replaced ./Nat/Zero
with ./True
.
Let's verify that this works by running the code through the morte
compiler:
$ morte
./three ./Bool ./not ./True
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
morte
computes that the number ./three
is not even, returning ./False
.
We can even go a step further and save an ./even
function to a file:
$ annah > even
(n : ./Nat ) →
n ./Bool
./not  Replace each `./Nat/Succ` with `./not`
./True  Replace each `./Nat/Zero` with `./True`
... and use our newlyformed ./even
function:
$ morte
./even ./three
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
$ morte
./even ./Nat/Zero
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
The annah
compiler actually provides direct support for natural number literals, so you can also just write:
$ annah  morte
./even 100
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
What about addition? How do we add two numbers using only substitution?
Well, one way we can add two numbers, m
and n
, is that we substitute each ./Nat/Succ
in m
with ./Nat/Succ
(i.e. keep them the same) and substitute the Zero
with n
. In other words:
$ annah > plus
λ(m : ./Nat ) → λ(n : ./Nat ) →
m ./Nat  The result will still be a `./Nat`
./Nat/Succ  Replace each `./Nat/Succ` with `./Nat/Succ`
n  Replace each `./Nat/Zero` with `n`
Let's verify that this works:
$ annah  morte
./plus 2 2
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ Zero)))
We get back a Churchencoded 4!
What happened under the hood was the following substitutions:
./plus 2 2
 Resolve `./plus`
= (λ(m : ./Nat ) → λ(n : ./Nat ) → m ./Nat ./Nat/Succ n) 2 2
 βreduce
= (λ(n : ./Nat ) → 2 ./Nat ./Nat/Succ n) 2
 βreduce
= 2 ./Nat ./Nat/Succ 2
 Definition of 2
= (./Nat/Succ (./Nat/Succ ./Nat/Zero )) ./Nat ./Nat/Succ 2
 Resolve and βreduce the definition of 2 (multiple steps)
= (λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ Zero)
) ./Nat ./Nat/Succ 2
 βreduce
= (λ(Succ : ∀(pred : ./Nat ) → ./Nat ) → λ(Zero : ./Nat ) →
Succ (Succ Zero)
) ./Nat/Succ 2
 βreduce
= (λ(Zero : ./Nat ) → ./Nat/Succ (./Nat/Succ Zero)) 2
 βreduce
= ./Nat/Succ (./Nat/Succ 2)
 Definition of 2
= ./Nat/Succ (./Nat/Succ (./Nat/Succ (./Nat/Succ ./Nat/Zero )))
 Resolve and βreduce (multiple steps)
= λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ Zero)))
So we can encode natural numbers in lambda calculus, albeit very inefficiently! There are some tricks that we can use to greatly speed up both the time complexity and constant factors, but it will never be competitive with machine arithmetic. This is more of a proof of concept that you can model arithmetic purely in code.
Exercise:Implement a function which multiplies two natural numbers
Data types
annah
also lets you define "temporary" data types that scope over a given expression. In fact, that's how Nat
was implemented. You can look at the corresponding *.annah
files to see how each type and term is defined in annah
before conversion to morte
code.
For example, here is how the Nat
type is defined in annah
:
$ cat Nat.annah
type Nat
data Succ (pred : Nat)
data Zero
fold foldNat
in Nat
The first four lines are identical to what we wrote when we invoked the annah types
command from the command line. We can use the exact same data type specification to create a scoped expression that can reference the type and data constructors we specified.
When we run this expression through annah
we get back the Nat
type:
$ annah < Nat.annah
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
You can use these scoped datatype declarations to quickly check how various datatypes are encoded without polluting your current working directory. For example, I can ask annah
how the type Maybe
is encoded in lambda calculus:
$ annah
λ(a : *) →
type Maybe
data Just (x : a)
data Nothing
 You can also leave out this `fold` if you don't use it
fold foldMaybe
in Maybe
λ(a : *) → ∀(Maybe : *) → ∀(Just : ∀(x : a) → Maybe) →
∀(Nothing : Maybe) → Maybe
A Maybe
value is just another substitution function. You provide one branch that you substitute for Just
and another branch that you substitute for Nothing
. For example, the Just
constructor always substitutes in the first branch and ignores the Nothing
branch that you supply:
$ annah
λ(a : *) →
type Maybe
data Just (x : a)
data Nothing
in Just
λ(a : *) → λ(x : a) → λ(Maybe : *) → λ(Just : ∀(x : a) → Maybe)
→ λ(Nothing : Maybe) → Just x
Vice versa, the Nothing
constructor substitutes in the Nothing
branch that you supply and ignores the Just
branch:
$ annah
λ(a : *) →
type Maybe
data Just (x : a)
data Nothing
in Nothing
λ(a : *) → λ(Maybe : *) → λ(Just : ∀(x : a) → Maybe) → λ(Nothing : Maybe) → Nothing
Notice how we've implemented Maybe
and Just
purely using functions. This implies that any language with functions can encode Maybe
, like Python!
Let's translate the above definition of Just
and Nothing
to the equivalent Python code. The only difference is that we delete the type abstractions because they are not necessary in Python:
def just(x):
def f(just, nothing):
return just(x)
return f
def nothing():
def f(just, nothing):
return nothing
return f
We can similarly translate Haskellstyle pattern matching like this:
example :: Maybe Int > IO ()
example m = case m of
Just n > print n
Nothing > return ()
... into this Python code:
def example(m):
def just(n): # This is what we substitute in place of `Just`
print(n)
def nothing(): # This is what we substitute in place of `Nothing`
return
m(just, nothing)
... and verify that our pattern matching function works:
>>> example(nothing())
>>> example(just(1))
1
Neat! This means that any algebraic data type can be embedded into any language with functions, which is basically every language!
Warning: your colleagues may get angry at you if you do this! Consider using a language with builtin support for algebraic data types instead of trying to twist your language into something it's not.
Let expressions
You can also translate let
expressions to lambda calculus, too. For example, instead of saving something to a file we can just use a let
expression to temporarily define something within a program.
For example, we could write:
$ annah  morte
let x : ./Nat = ./plus 1 2
in ./plus x x
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ (Succ (Succ Zero)))))
... but that doesn't really tell us anything about how annah
desugars let
because we only see the final evaluated result. We can ask annah
to desugar without performing any other transformations using the annah desugar
command:
$ annah desugar
let x : ./Nat = ./plus 1 2
in ./plus x x
(λ(x : ./Nat ) → ./plus x x) (./plus (λ(Nat : *) → λ(Succ :
∀(pred : Nat) → Nat) → λ(Zero : Nat) → Succ Zero) (λ(Nat : *) →
λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) → Succ (Succ
Zero)))
... which makes more sense if we clean up the result through the use of numeric literals:
(λ(x : ./Nat ) → ./plus x x) (./plus 1 2)
Every time we write an expression of the form:
let x : t = y
in e
... we decode that to lambda calculus as:
(λ(x : t) → e) y
We can also decode function definitions, too. For example, you can write:
$ annah  morte
let increment (x : ./Nat ) : ./Nat = ./plus x 1
in increment 3
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ Zero)))
... and the intermediate desugared form also encodes the function definition as a lambda expression:
$ annah desugar
let increment (x : ./Nat ) : ./Nat = ./plus x 1
in increment 3
(λ(increment : ∀(x : ./Nat ) → ./Nat ) → increment (λ(Nat : *)
→ λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) → Succ (Succ
(Succ Zero)))) (λ(x : ./Nat ) → ./plus x (λ(Nat : *) → λ(Succ
: ∀(pred : Nat) → Nat) → λ(Zero : Nat) → Succ Zero)
... which you can clean up as this expression:
(λ(increment : ∀(x : ./Nat ) → ./Nat ) → increment 3)
(λ(x : ./Nat ) → ./plus x 1)
We can combine let
expressions with data type expressions, too. For example, here's our original not
program, except without saving anything to files:
$ annah
type Bool
data True
data False
fold if
in
let not (b : Bool) : Bool = if b Bool False True
in
not False
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → True
Lists
annah
also provides syntactic support for lists as well. For example:
$ annah
[nil ./Bool , ./True , ./False , ./True ]
λ(List : *) → λ(Cons : ∀(head : ./Bool ) → ∀(tail : List) →
List) → λ(Nil : List) → Cons ./True (Cons ./False (Cons
./True Nil))
Just like all the other data types, a list is defined in terms of what you use to substitute each Cons
and Nil
constructor. I can replace each Cons
with ./and
and the Nil
with ./True
like this:
$ annah  morte
[nil ./Bool , ./True , ./False , ./True ] ./Bool ./and ./True
∀(Bool : *) → ∀(True : Bool) → ∀(False : Bool) → Bool
λ(Bool : *) → λ(True : Bool) → λ(False : Bool) → False
This conceptually followed the following reduction sequence:
( λ(List : *)
→ λ(Cons : ∀(head : ./Bool ) → ∀(tail : List) → List)
→ λ(Nil : List)
→ Cons ./True (Cons ./False (Cons ./True Nil))
) ./Bool
./and
./True
 βreduction
= ( λ(Cons : ∀(head : ./Bool ) → ∀(tail : ./Bool ) → ./Bool )
→ λ(Nil : ./Bool )
→ Cons ./True (Cons ./False (Cons ./True Nil))
) ./and
./True
 βreduction
= ( λ(Nil : ./Bool )
→ ./and ./True (./and ./False (./and ./True Nil))
) ./True
 βreduction
= ./and ./True (./and ./False (./and ./True ./True))
Similarly, we can sum a list by replacing each Cons
with ./plus
and replacing each Nil
with 0
:
$ annah  morte
[nil ./Nat , 1, 2, 3, 4] ./Nat ./plus 0
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
Zero)))))))))
This behaves as if we had written:
./plus 1 (./plus 2 (./plus 3 (./plus 4 0)))
Prelude
annah
also comes with a Prelude to show some more sophisticated examples of what you can encode in pure lambda calculus. You can find version 1.0 of the Prelude here:
http://sigil.place/prelude/annah/1.0/
You can use these expressions directly within your code just by referencing their URL. For example, the remote Bool
expression is located here:
http://sigil.place/prelude/annah/1.0/Bool/@
... and the remote True
expression is located here:
http://sigil.place/prelude/annah/1.0/Bool/True
... so we can check if the remote True
's type matches the remote Bool
by writing this:
$ annah
http://sigil.place/prelude/annah/1.0/Bool/True : http://sigil.place/prelude/annah/1.0/Bool
http://sigil.place/prelude/annah/1.0/Bool/True
$ echo $?
0
Similarly, we can build a natural number (very verbosely) using remote Succ
and Zero
:
$ annah  morte
http://sigil.place/prelude/annah/1.0/Nat/Succ
( http://sigil.place/prelude/annah/1.0/Nat/Succ
( http://sigil.place/prelude/annah/1.0/Nat/Succ
http://sigil.place/prelude/annah/1.0/Nat/Zero
)
)
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ Zero))
However, we can also locally clone the Prelude using wget
if we wish to refer to local file paths instead of remote paths:
$ wget np r cutdirs=3 http://sigil.place/prelude/annah/1.0/
$ cd sigil.place
$ ls
(>) Defer.annah List.annah Path Sum0.annah
(>).annah Eq Maybe Path.annah Sum1
Bool Eq.annah Maybe.annah Prod0 Sum1.annah
Bool.annah Functor Monad Prod0.annah Sum2
Category Functor.annah Monad.annah Prod1 Sum2.annah
Category.annah index.html Monoid Prod1.annah
Cmd IO Monoid.annah Prod2
Cmd.annah IO.annah Nat Prod2.annah
Defer List Nat.annah Sum0
Now we can use these expressions using their more succinct local paths:
./Nat/sum (./List/(++) ./Nat [nil ./Nat , 1, 2] [nil ./Nat , 3, 4])
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
Zero)))))))))
Also, every expression has a corresponding *.annah
file that documents the expression's type using a let
expression. For example, we can see the type of the ./List/(++)
function by studying the ./List/(++).annah
file:
cat './List/(++).annah'
let (++) (a : *) (as1 : ../List a) (as2 : ../List a) : ../List a =
(List : *)
> (Cons : a > List > List)
> (Nil : List)
> as1 List Cons (as2 List Cons Nil)
in (++)
The top line tells us that (++)
is a function that takes three arguments:

An argument named
a
for the type list elements you want to combine 
An argument named
as1
for the left list you want to combine 
An argument named
as2
for the right list you want to combine
... and the function returns a list of the same type as the two input lists.
Beyond
Exactly how far can you take lambda calculus? Well, here's a program written in annah
that reads two natural numbers, adds them, and writes them out:
$ annah  morte
./IO/Monad ./Prod0 (do ./IO {
x : ./Nat < ./IO/get ;
y : ./Nat < ./IO/get ;
_ : ./Prod0 < ./IO/put (./Nat/(+) x y);
})
∀(IO : *) → ∀(Get_ : ((∀(Nat : *) → ∀(Succ : ∀(pred : Nat) →
Nat) → ∀(Zero : Nat) → Nat) → IO) → IO) → ∀(Put_ : (∀(Nat : *)
→ ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat) → IO →
IO) → ∀(Pure_ : (∀(Prod0 : *) → ∀(Make : Prod0) → Prod0) → IO)
→ IO
λ(IO : *) → λ(Get_ : ((∀(Nat : *) → ∀(Succ : ∀(pred : Nat) →
Nat) → ∀(Zero : Nat) → Nat) → IO) → IO) → λ(Put_ : (∀(Nat : *)
→ ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat) → IO →
IO) → λ(Pure_ : (∀(Prod0 : *) → ∀(Make : Prod0) → Prod0) → IO)
→ Get_ (λ(r : ∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) →
∀(Zero : Nat) → Nat) → Get_ (λ(r : ∀(Nat : *) → ∀(Succ :
∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat) → Put_ (λ(Nat : *)
→ λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) → r@1 Nat Succ
(r Nat Succ Zero)) (Pure_ (λ(Prod0 : *) → λ(Make : Prod0) →
Make))))</</</
This does not run the program, but it creates a syntax tree representing all program instructions and the flow of information.
annah
supports do
notation so you can do things like write list comprehensions in annah
:
$ annah  morte
./List/sum (./List/Monad ./Nat (do ./List {
x : ./Nat < [nil ./Nat , 1, 2, 3];
y : ./Nat < [nil ./Nat , 4, 5, 6];
_ : ./Nat < ./List/pure ./Nat (./Nat/(+) x y);
}))
∀(Nat : *) → ∀(Succ : ∀(pred : Nat) → Nat) → ∀(Zero : Nat) → Nat
λ(Nat : *) → λ(Succ : ∀(pred : Nat) → Nat) → λ(Zero : Nat) →
Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ (Succ
(Succ (Succ (Succ Zero)))))))))))))))))))))))))))))))))))))))))
)))))))))))))))))))))
The above Annah program is equivalent to the following Haskell program:
sum (do
x < [1, 2, 3]
y < [4, 5, 6]
return (x + y) )</</
... yet it is implemented 100% in a minimal and total lambda calculus without any builtin support for data types.
This tutorial doesn't cover how do
notation works, but you can learn this and more by reading the Annah tutorial which is bundled with the Hackage package:
Conclusions
A lot of people underestimate how much you can do in a total lambda calculus. I don't recommend pure lambda calculus as a general programming language, but I could see a lambda calculus enriched with highefficiency primitives to be a realistic starting point for simple functional languages that are easy to port and distribute.
One of the projects I'm working towards in the long run is a "JSON for code" and annah
is one step along the way towards that goal. annah
will likely not be that language, but I still factored out annah
as a separate and reusable project along the way so that others could fork and experiment with annah
when experimenting with their own language design.
Also, as far as I can tell annah
is the only project in the wild that actually implements the BoehmBerarducci encoding outlined in this paper:
... so if you prefer to learn the encoding algorithm by studying actual code you can use the annah
source code as a reference realworld implementation.
You can find Annah project on Hackage or Github:
... and you can find the Annah prelude hosted online:
The Annah tutorial goes into the Annah language and compiler in much more detail than this tutorial, so if you would like to learn more I highly recommend reading the tutorial which walks through the compiler, desugaring, and the Prelude in much more detail:
Also, for those who are curious, both the annah
and morte
compilers are named after characters from the game Planescape: Torment.